Brand Trust, Customer Relationship Dan Lokasi Penjualan Pada Keputusan Pembelian Produk Batik Tulis Khas Trowulan - Idris, Hilmy Fachrudin; Setiawan, Erry; Sigita, Dwi Sembe (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2024)
This study aims to analyze the influence of brand trust, customer relationship and location on the purchase decision of Trowulan typical handwritten batik home industry products in Mojokerto partially, simultaneously and dominantly. The population in this study is all people who have purchased or ordered Trowulan typical handwritten batik home industry products in Mojokerto, which is as many as 220 people. The sample was determined by the slovin formula and non-probability sampling technique, so that the research sample with 141 respondents. The data collection methods used are observation, interview, and questionnaire methods. The data analysis methods used in this study are validity test methods, reliability tests, classical assumption tests, normality tests, heteroscedasticity tests, autocorrelation tests, and multicollinearity tests as well as hypothesis tests that include the t test and F test. Based on the results of the research as follows: 1) There is an influence of brand trust on the purchase decision of Trowulan typical handwritten batik home industry products in Mojokerto, 2) There is an influence of customer relationship on the purchase decision of Trowulan typical handwritten batik home industry products in Mojokerto, 3) There is an influence on location with the decision to purchase home industry products Trowulan handwritten batik in Mojokerto, 4) There is an influence of brand trust, customer relationship, and location simultaneously on the purchase decision of Trowulan typical handwritten batik home industry products in Mojokerto, 5) Of the variables of brand trust, customer relationship and location that have a dominant influence are location variables.